The Effectiveness of Acceptance and Commitment Therapy (ACT) on Depression, Anxiety and Stress Syndrome in Patients with Gender Dysphoria Disorder - Osaty Araghi, Katayoon; Saleh, Mahdieh (International Journal of Psychosocial Rehabilitation, 2021)
Introduction: The aim of the present study was to determine the effectiveness of Acceptance and Commitment Therapy (ACT) therapy on depression, anxiety and stress syndrome in patients with Gender Dysphoria Disorder. Method: The present study is a quasi-experimental study based on pretest-posttest design with experimental group. The statistical population of this study is all patients with female sexual dysfunction referred to the Institute of Psychiatry in Tehran in the second half of the year 2017 whom are proved by medical records constitute gender dysphoria disorder and Thirty of them were selected by convenience sampling and randomly assigned to experimental and control groups, then answered to the Anxiety, Depression and Stress Questionnaire (Lovebound & Lovebound, 1995) before and after the intervention. Results: The results of multivariate covariance test showed that ACT intervention was effective in reducing anxiety, depression and stress in patients with gender dysphoria. Conclusion: Therefore, the results showed that ACT therapy can be used in the treatment of some disorders of gender dysphoria patients